OP20 Cardiovascular disease biomarker profiles among harmful and hazardous drinkers: a cross-sectional study from north west russia. (3rd September 2019) - Iakunchykova, O; Averina, M; Kudryavtsev, A; Soloviev, A; Wilsgaard, T; Leon, DA
Abstract : Background: Heavy alcohol drinking is increasingly recognized as a risk factor for cardiovascular disease (CVD), although the mechanisms underlying this are not well understood. Moderate alcohol consumption is associated with changes in many blood biomarkers of cardiometabolic risk. There are however few studies of the impact of harmful and hazardous drinking on CVD biomarkers. We conducted a study in Russia to explore the association between levels of heavy alcohol consumption on biomarkers of cardiac damage. Methods: The Know Your Heart study recruited and medically examined a random sample of 2354 participants from the general population of Arkhangelsk city (NW Russia) plus 271 participants from the Regional Psychiatric hospital alcohol treatment facility with a primary diagnosis of alcohol problems. Measurements were made of (i) high sensitivity Troponin T (hsTroponinT), a marker of cardiac damage, (ii) N-terminal pro-B-type natriuretic peptide (NT-Pro-BNP), a marker cardiac wall stretch, and (iii) high sensitivity C-reactive protein (hsCRP), a marker of systemic inflammation. Their concentrations were compared between the patients from the alcohol treatment facility and the general population sample divided according to levels of harmful/hazardous drinking. The associations between heavy alcohol use and log-transformed biomarkers were estimated using multivariate linear regression models adjusted for directed acyclic graphs specified minimal sufficient set of confounders: age, sex, smoking and education. Results: Those in the alcohol treatment facility had the highest levels of all three biomarkers relative to non-hazardous drinkers in the general population: hsTroponinT was elevated by 10.3% (95%CI: 3.7%, 17.4%), NT-Pro-BNP - by 46.7% (95%CI: 26.8%, 69.8%), hsCRP - by 69.2% (95%CI: 43%, 100%). NT-Pro-BNP was also elevated, but to a smaller degree, for harmful drinkers in the general population – by 31.5% (95%CI: 3.4, 67.2). A trend test across categories of drinkers was significant for NT-Pro-BNP and hsCRP with concentration of biomarkers going up with higher levels of alcohol exposure (p<0.001). Conclusion: The key finding is that NT-Pro-BNP was raised in both patients in the alcohol treatment facility and among harmful drinkers in the general population. This biomarker of pathological wall stress is a predictor of CVD events. This consistent finding in the two groups supports the hypothesis that heavy alcohol drinking has an adverse effect on cardiac structure and function and may thus lead to increased risk of CVD. However, the importance for CVD of the marked elevation of hsCRP in the alcohol treatment group is less clear.